Role of Ectodermal-neural cortex 1 protein in human glioma progression, identification of a peptide internalized by human glioblastoma cells and development of an alternative method to generate growth curves of adherent cultures - Pereira, Túlio Felipe (2018)
Gliomas are the most common form of primary intracranial malignancy, among which astrocytomas are the most frequent. Ectodermal-cortex protein 1 (ENC 1), also known as Nuclear Restricted Protein/Brain (NRP/B), was first characterized as a protein which interacts with the cytoskeleton by binding to actin through Kelch-like domains, being related to neural fate specification during development of the nervous system. The first chapter of this thesis confirms ENC1 as a tumor suppression properties by a genomic edition approach, analyses ENC1 expression in a set of patient glioma samples and describes the correlation these data with patients survival and progression-free survival, concluding that ENC1 expression may constitute a biomarker for glioma aggressiveness. The second chapter refers to the identification and in vitro characterization of the LHTNELQ peptide, which was selected by the Phage Display method using human glioblastoma cells. This new peptide is able to be internalized by these cells and features as a new tool for the development of glioma therapeutics. The third chapter report an alternative method to generate growth curves of adherent cell cultures, which is based on the CFSE fluorescence decay over time. It is an alternative method to determine growth curves of cultured cells, with smaller variation among technical replicates than that of counting-based methods.